Development of a Website-Based Online Health Screening and Education Database Related to Noncommunicable Diseases (NCDs) in Realizing Health Promoting University - Reskiaddin, La Ode; Aswin, Budi; Siregar, Sri Astuti; Prasetyo, Yodi (Universitas Airlangga, 2025)
Background: The use of website-based reporting in reporting screening databases and health services is still rarely used and developed in educational institutions. Websites can also be used as educational services to increase literacy and knowledge of the community, especially the academic community. Objectives: This research aims to develop a website database for noncommunicable disease screening and website-based health education to create a healthy campus. This is in line with the increasing trend of noncommunicable diseases in the university setting. Method: This research uses a quantitative R&D model approach by implementing several development stages. The informants in this study numbered 23, consisting of three experts for website assessment and 20 website users who were selected purposively. Results: The research results showed that the need assessment of a website entailed a) Information systems can be used as a medium for health-related education, especially those related to noncommunicable diseases, b) Information systems are used to record visits by Posbindu participants, c) Information systems are used to process and display data on risk factors for noncommunicable diseases, and d) Information systems process and display information related to healthy campuses. The average assessment validation of professionals was 94.07% (very feasible), and participants validation was 91.44% (very feasible). Conclusion: Development of a noncommunicable disease screening database website and website-based health education to make a healthy campus a viable medium for providing health information.